2010
DOI: 10.1073/pnas.1012999107
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of protein oligomerization, the critical role of insertions and deletions in maintaining different oligomeric states

Abstract: The main principles of protein-protein recognition are elucidated by the studies of homooligomers which in turn mediate and regulate gene expression, activity of enzymes, ion channels, receptors, and cell-cell adhesion processes. Here we explore oligomeric states of homologous proteins in various organisms to better understand the functional roles and evolutionary mechanisms of homooligomerization. We observe a great diversity in mechanisms controlling oligomerization and focus in our study on insertions and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
148
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(159 citation statements)
references
References 60 publications
6
148
0
5
Order By: Relevance
“…Perturbations within the loop structure were detected in NMR studies with a mutant of RKIP, which at least partially imitates a phosphorylation at this site (RKIP S153E ) (14). Further observations by others strengthen our assumption that this loop represents the interface for RKIP dimerization: loops in general often participate in protein-protein interactions (45,46); particularly, loops with a relatively high fraction of polar, charged residues, as well as glycines and prolines have been suggested to be involved in protein dimerization (37,47). Indeed, loop 127-150 contains eight charged and eight polar amino acids, as well as two glycines and two prolines of 24 amino acids; Banfield et al (8) have generated crystals of dimeric hRKIP and suggested this loop as a putative dimer interface.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Perturbations within the loop structure were detected in NMR studies with a mutant of RKIP, which at least partially imitates a phosphorylation at this site (RKIP S153E ) (14). Further observations by others strengthen our assumption that this loop represents the interface for RKIP dimerization: loops in general often participate in protein-protein interactions (45,46); particularly, loops with a relatively high fraction of polar, charged residues, as well as glycines and prolines have been suggested to be involved in protein dimerization (37,47). Indeed, loop 127-150 contains eight charged and eight polar amino acids, as well as two glycines and two prolines of 24 amino acids; Banfield et al (8) have generated crystals of dimeric hRKIP and suggested this loop as a putative dimer interface.…”
Section: Discussionsupporting
confidence: 53%
“…They promote conformational changes and alter surface properties of proteins and may thereby affect protein-protein interactions, activation/ inhibition of enzyme activity, or self-association. Self-association of proteins can increase protein stability and generate new binding sites and thus alter protein function (37)(38)(39)(40)(41)(42)(43). Surprisingly, homo-oligomerization as an efficient mechanism to control protein-protein interactions has thus far not been taken into consideration for RKIP.…”
Section: Discussionmentioning
confidence: 99%
“…In biomedical products, for example pharmaceutical formulations, chemicals or co-solvents can be added to either stabilize or compete with contacts between proteins [76]. Oligomerization of proteins can also be modified by changing the primary sequence of the protein at specific protein-coupling interfaces [76,77]. These changes will, of course, affect entire protein populations.…”
Section: Discussionmentioning
confidence: 99%
“…Homo-oligomeric proteins are a source of diversity and structural specificity under intensive study for a better understanding of their functional roles in providing stability and protection against denaturation and for the elucidation of the mechanisms involved in the evolution of structure-function (Hashimoto and Panchenko, 2010). In this regard, the MDH enzyme has been widely used as a model because of its presence in different subcellular compartments and as different functional oligomeric states (dimers or tetramers).…”
Section: Molecular Evolution Of Bacterial Malate Dehydrogenasementioning
confidence: 99%